Analysis of historic changes in regional ecosystem service provisioning using land use data - Lautenbach, Sven; Lausch, Angela; Seppelt, Ralf (Ecological indicators, 2011)
Land use change has a major impact on goods and services that our environment supplies for society. While detailed ecological or biophysical field studies are needed to quantify the exact amount of ecosystem service supply at local scales, such a monitoring might be unfeasible at the regional scale. Since field scale monitoring schemes for ecosystem services or ecosystem functioning are missing, proxy based indicators can help to assess the historic development of ecosystem services or ecosystem functioning at the regional scale. We show at the example of the historic development (1964-2004) in the district of Leipzig/Germany how land use/land cover data can be used to derive regional scale indicators for ecosystem functions. We focus thereby on two hypotheses: (1) the ecosystem functioning has degraded over time and (2) changes in land use configuration play an important role in this degradation. The study focuses on indicators for ecosystem functions related to (i) water purification by riparian buffer strips, (ii) pollination, (iii) food production and (iv) outdoor recreation. Each indicator builds on the analysis of land use configuration and land use composition information and is tested on sensitivity/robustness with respect to parameters which had to be estimated based on expert knowledge. We show that land use composition is an important aspect in our ecosystem service assessment. Although our study region is faced with a maximum land use change of 11% in the major land use classes between 1964 and 2004, we see a decrease of ecosystem function indicators up to 23%. The regional assessment shows an overall trend for degradation of ecosystem functioning from 1964 to 1984. This trend is reversed between 1984 and 1994 but the process slowed down until 2004 without reaching the level of 1964.